Experimental study on the feasibility assessment of using biopolymer-treated clays as a slurry material for TBM excavation - Lee, Sojeong; Chang, Ilhan (Smart Geotechnics for Smart Societies, 2023)
Bentonite-based slurry is commonly used for tunnel boring machine (TBM) excavation practices. However, the use of bentonite-based slurry accompanies environmental concerns and expansive after-use treatments. Meanwhile, biopolymer-based soil treatment (BPST) has been recently introduced to geotechnical engineering and has shown promising effects including shear strength increase, hydraulic conductivity decrease. In a previous study, xanthan gum biopolymer was attempted as a possible slurry substitute for mechanical tunneling. Biopolymer-based hybrid slurry mixtures were tested through a series of experimental programs including rheology assessment, hydraulic conductivity measurement, and swelling behavior assessment. As a result, biopolymer-based hybrid slurry has shown high competitiveness and feasibility to be used as a slurry material during TBM excavation.